Analysis of Shopee Pay Digital Payment Adoption in Jakarta with Innovation Diffusion Theory - Aditya, Ricky; Rivaldi, Rahmad; Al Mizan, Rama; Romadhon, Ismi Amalia; Nofitra, Muhammad Ilham (FKIP Universitas Lampung, 2024)
The increase in internet users has significantly impacted people's behaviour patterns in making payment transactions from offline to online. One of the dominating online or digital payment systems with a large number of e-wallet users and frequency is Shopee Pay. The dominance of this application, which quickly outperforms its competitors, is inseparable from its users' good acceptance of something new. Technological diffusion theory explained how an innovation is adopted over time by examining the decision to adopt the process. Therefore, this research aimed to determine the factors affecting Shopee Pay services adoption in Jakarta.Data were collected from 100 Shopee Pay users in Jakarta. The descriptive statistics and statistical data analysis using Smart PLS software were carried out for outer and inner model analysis and hypothesis testing. The results showed that Relative Advantage, Observability and Perceived Risk significantly affect adoption. In contrast, Compatibility, Complexity, and Trialability have an insignificant effect on adoption. Number of respondent, coverage area of the survey and period of research. Future research is expected to be able to use other models besides the Diffusion of Innovation Theory to better identify other additional factors capable of affecting the adoption of Shopee Pay digital payment services and Shopee Pay digital payment is recommended to offer services that are more compatible with various lifestyle needs and beliefs to meet the expectations of current users. This survey has difference with previous research because of adoption level of digital payment specifically focus on Shopee Pay then using Innovation Diffusion Theory as model of research.Keywords: Information Technology Adoption, Digital Payment, Innovation Diffusion TheoryDOI: http://dx.doi.org/10.23960/E3J/v7i1.18-27